Recognition and Identification: The Constitution of the Subject in Hegelian Dialectics and the Lacanian Mirror Stage (Interapia – Journal of Clinic, Culture and Mental Sciences, 2025)
Abstract This paper examines the constitution of the subject through the articulation between Hegel’s dialectics of recognition and Lacan’s mirror stage. A systematic literature review (SciELO, PubMed, PsycINFO, Philosopher’s Index, 2020–2025) explored identification, alienation, and subjectivity. Findings indicate that alienation functions as a structuring force in ego formation, generating narcissistic defenses and secondary identifications. The convergence between Hegel and Lacan frames recognition as a symbolic and imaginary process mediated by language, power, and otherness. The study concludes that integrating philosophy and psychoanalytic clinical practice enriches the understanding of mourning, resistance, and subjective reconstruction, with ethical and therapeutic implications.
Keywords: Recognition; Identification; Subjectivity; Hegel; Lacan.